Koreksi Malposisi Gigi Insisivus Rahang Bawah dengan Menggunakan Alat Orthodontic Lepasan - Anastasia Mayang Cahyani; Bramita Beta Arnanda (Lembaga Pengembangan Kinerja Dosen, 2026)
Introduction: Malocclusion is an abnormal alignment of the teeth and an improper relationship between the maxillary and mandibular teeth in centric occlusion, which may affect mastication, speech, swallowing, and facial esthetics. Removable orthodontic appliances are commonly used for mild to moderate malocclusion cases, although treatment success greatly depends on patient compliance. Objective: This case report aims to describe the management of removable orthodontic treatment in correcting mandibular anterior tooth malposition. Case Report: A 24-year-old female patient presented to Soelastri Dental Hospital, Surakarta, with a complaint of crowded lower anterior teeth causing food impaction and reduced self-confidence. Clinical examination revealed Angle Class I malocclusion modified by Dewey type 1 with skeletal Class I relationship, spacing between teeth 23–24 and 24–25, and individual tooth malpositions, particularly in the mandibular anterior region. Case Management: Treatment was performed using maxillary and mandibular removable orthodontic appliances with continuous spring, finger spring, selective grinding, and periodic activations over five control visits. Discussion: Improvement in the alignment of the four mandibular incisors was observed through orthodontic tooth movement and alveolar bone remodeling. However, the correction was not fully optimal due to inadequate patient compliance in wearing the appliance. Conclusion: Removable orthodontic appliances are effective for mild to moderate malposition correction when used consistently and accompanied by regular follow-up visits.Conclusion: Improvement in tooth malposition was observed, although the result was not yet optimal, most likely due to inadequate patient compliance in wearing the appliance.